The Implementation of Special Allocation Fund Policy for Rural Transportation Sector - Wasifah Hanim (Faculty of Economics, Universitas Sriwijaya, 2018)
The implementation of regional autonomy that has been rolled out since 1999 attempts to reduce inequality between regions through balancing funds, including through Special Allocation Fund (SAF). Several fund allocations sourced from SAF have been rolled out by the government such as SAF for rural transportation. SAF for rural transportation is a type of SAF that aims to ensure the adequate mobility of society and the distribution of goods/services through the provision of regional transportation facilities in the growth centers of areas that have potential base sector. Using secondary data, this paper attempts to analyze the distribution of SAF for rural transportation in disadvantaged areas, border areas, and outlying islands. based on the results of the analysis shows that the allocation side of SAF recipient regions, it indicates that the priority of infrastructure development originating from SAF for Rural Transportation is for lagging districts/cities, border areas, and outer islands.